2019
DOI: 10.1111/iju.14041
|View full text |Cite
|
Sign up to set email alerts
|

Particle therapy for prostate cancer: The past, present and future

Abstract: Although prostate cancer control using radiotherapy is dose‐dependent, dose–volume effects on late toxicities in organs at risk, such as the rectum and bladder, have been observed. Both protons and carbon ions offer advantageous physical properties for radiotherapy, and create favorable dose distributions using fewer portals compared with photon‐based radiotherapy. Thus, particle beam therapy using protons and carbon ions theoretically seems suitable for dose escalation and reduced risk of toxicity. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 59 publications
(143 reference statements)
0
27
0
Order By: Relevance
“…Several randomized trials and meta-analyses performed in the 1990s and 2000s showed a significant benefit of androgen deprivation therapy (ADT) combined with RT in terms of biochemical control and overall survival (OS) among patients with intermediate-risk and high-risk PC [4][5][6][7]. Because the relatively low irradiation doses (65-70 Gy) were used in those trials, the optimal duration of ADT to use in combination with high-dose RT remains unknown [8]. Since ADT has negative impacts on bone, lipid, and glucose metabolism and increases the risks of bone fractures, metabolic syndrome, and diabetes mellitus [9][10][11], it is desirable to perform the minimum ADT necessary to control PC.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized trials and meta-analyses performed in the 1990s and 2000s showed a significant benefit of androgen deprivation therapy (ADT) combined with RT in terms of biochemical control and overall survival (OS) among patients with intermediate-risk and high-risk PC [4][5][6][7]. Because the relatively low irradiation doses (65-70 Gy) were used in those trials, the optimal duration of ADT to use in combination with high-dose RT remains unknown [8]. Since ADT has negative impacts on bone, lipid, and glucose metabolism and increases the risks of bone fractures, metabolic syndrome, and diabetes mellitus [9][10][11], it is desirable to perform the minimum ADT necessary to control PC.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients can nowadays select several modalities in radiotherapy such as conventional X-ray therapy and particle therapies (e.g., proton therapy, heavy ion therapy and boron neutron capture therapy). The number of patients receiving particle therapy for cancer (mainly proton or C-ion beams) is increasing annually 1 . There are two major advantages to particle therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Proton beam therapy (PBT) is a promising curative therapy for localized prostate cancer as well as surgical resection and other radiation therapies (RTs) such as intensity-modulated radiation therapy and heavy particle therapy [ 1 ]. In Japan, national health insurance has covered PBT since April 2018 and the number of treatment facilities has increased.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, national health insurance has covered PBT since April 2018 and the number of treatment facilities has increased. PBT for prostate cancer reduces the incidence of late toxicity because of smaller radiation doses and volumes directed at the organs at risk surrounding the prostate [ 1 ]. However, one of the relatively frequent adverse events following PBT treatment is lower urinary tract symptoms (LUTS).…”
Section: Introductionmentioning
confidence: 99%